2017
DOI: 10.1016/j.jdermsci.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of omalizumab in Japanese and Korean patients with refractory chronic spontaneous urticaria

Abstract: The POLARIS study demonstrates that omalizumab is an efficacious and well-tolerated add-on therapy in Japanese and Korean H1AH-refractory patients with CSU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 37 publications
7
65
3
Order By: Relevance
“…Phases II-IV clinical trials have consistently demonstrated the efficacy and safety of omalizumab in patients with CSU unresponsive to standard or increased doses of AHs. A summary of the data from pivotal phases II-IV trials is given in Table 2 [31][32][33][34][35][36][37][38][39][40]. Numerous real-life studies have confirmed these findings.…”
Section: Omalızumab: From Development To Current Challengesmentioning
confidence: 88%
“…Phases II-IV clinical trials have consistently demonstrated the efficacy and safety of omalizumab in patients with CSU unresponsive to standard or increased doses of AHs. A summary of the data from pivotal phases II-IV trials is given in Table 2 [31][32][33][34][35][36][37][38][39][40]. Numerous real-life studies have confirmed these findings.…”
Section: Omalızumab: From Development To Current Challengesmentioning
confidence: 88%
“… 17 The efficacy and safety of omalizumab in the treatment of CU has been demonstrated in many studies to date. 1 17 18 19 20 21 22 23 24 Omalizumab received US Food and Drug Administration approval as an add-on therapy for H 1 -antihistamine-refractory urticaria in 2014. In Korea, it was approved as an additional therapy in this patient group by the Ministry of Food and Drug Safety in 2017, based on the results of 1 randomized controlled trial (RCT) conducted in Korea and Japan.…”
Section: Omalizumabmentioning
confidence: 99%
“…In Korea, it was approved as an additional therapy in this patient group by the Ministry of Food and Drug Safety in 2017, based on the results of 1 randomized controlled trial (RCT) conducted in Korea and Japan. 18 …”
Section: Omalizumabmentioning
confidence: 99%
See 2 more Smart Citations